Compact High Gain Wideband Circularly Polarized Non-Uniform Metasurface Antenna Through Improved Mode Coupling - Komal Iqbal; Qasim Umar Khan; Zubair Ahmed (IEEE Open Journal of Antennas and Propagation)
A wideband, high gain circularly polarized (CP) metasurface (MTS) based slot antenna is presented. The designed nonuniform slots provide wider bandgap regions and extra degree of freedom in tuning to obtain wider impedance bandwidth through improved mode coupling for fixed optimum feed location along with improved 3-dB axial ratio bandwidth and gain. The extra radiation edges provided by nonuniform slots within the unit cell help in improving mode coupling thus resulting in increased performance of the designed antenna. Improved mode coupling in case of the proposed antenna is explained and verified using characteristic mode analysis (CMA). The proposed antenna with a small size of 0.8 x 0.8 x $0.079~λ _{0}^{3}~(λ _{0}$ at 6 GHz) is designed. Based on the proposed analysis, an antenna having wide impedance bandwidth of 48.74% (5.74-9.44 GHz), and a 3-dB axial ratio (AR) bandwidth of 19.92% (6.19-7.56 GHz) with a peak gain of 9.35 dBi is designed. In addition, a 2 x 2 array of proposed MTS is designed and fabricated. The MTS array has a peak gain of 14.45dBi with a 3-dB AR bandwidth of 61.75% and impedance bandwidth of 71.71%. The proposed antennas find good use in WiMAX, C-band, and radars applications.